The poetry lesson - Codrescu, Andrei, 1946- (Princeton University Press, 2010)
"Intro to Poetry Writing is always like this: a long labor, a breech birth, or, obversely, mining in the dark. You take healthy young Americans used to sunshine (aided sometimes by Xanax and Adderall), you blindfold them and lead them by the hand into a labyrinth made from bones. Then you tell them their assignment: 'Find the Grail. You have a New York minute to get it.'"--The Poetry LessonThe Poetry Lesson is a hilarious account of the first day of a creative writing course taught by a "typical fin-de-siècle salaried beatnik"--one with an antic imagination, an outsized personality and libido.